Optimisation of parameters for detection of manganese ion using electrochemical method. (August 2019) - Gilbert, R; Siddiquee, S; Saallah, S; Lal, Tamrin M
Abstract: An electrochemical method was detected a heavy metal ion of manganese (Mn 2+ ) based on bare gold electrode (AuE). The bare AuE was optimized including various type of electrolytes, redox indicators, pH, scan rate and accumulation time using cyclic voltammetry (CV). From the CV results, the optimal conditions of Mn 2+ were found of Tris-HCl (0.1 M, pH 2) buffer for electrolytes supported by 5 mM Prussian blue as a redox indicator with scan rate of 100 mVs-1 and accumulation time of 2 s, respectively. Differential pulse voltammetry (DPV) method was detected with different concentrations of Mn 2+ on the ranged from 0.05 to 1.0 ppm with limit of detection (LOD) of 0.075 mg L −1 (S/N=3). A linear regression was found of 0.9659 (r 2 ). The above results indicated that the bare AuE was unable to detect of Mn 2+ below safety level. So, the proposed method suggests to detect below safety level of Mn 2+ based on the further modification of AuE with high sensitivity, selectivity and accuracy.